Natural, longitudinal recovery of adults with COVID-19 using standardized rehabilitation measures - Ciro, Carrie A.; James, Shirley A.; McGuire, Hillary; Lepak, Vince; Dresser, Susan; Costner-Lark, Amy; Robinson, Wanda; Fritz, Terrie (Frontiers in Aging Neuroscience, 2022)
Background: While studies recommend rehabilitation following post-hospitalization recovery from COVID-19, few implement standardized tools to assess continued needs. The aim of this study was to identify post-hospitalization recommendations using an interdisciplinary needs assessment with standardized rehabilitation measures. A secondary aim was to use these tools to measure recovery over a 30-day period. Methods: Using a 30-day longitudinal design, we completed weekly rapid needs assessments in this convenience sample of 20 people diagnosed with COVID-19 discharged from the hospital to home. We computed summary statistics and used the Wilcoxon Signed Rank Test to assess change over the four-week course of the study with alpha level = 0.05. Results: Our sample (65% male, 47% over 50 years of age, 35% White, 37% with a confirmed diagnosis of diabetes, and 47% obese) included no patients who had required mechanical ventilation. Initial assessments demonstrated the majority of our participants were at an increased risk of falls, had disability in activities of daily living (ADL) and instrumental activities of daily living (IADL), mild cognitive impairment and dyspnea. At the 30-day follow-up, most were independent in mobility and basic ADLs, with continued disability in IADLs and cognitive function. Discussion: In this sample of patients who were not mechanically-ventilated, early and individualized rehabilitation was necessary. The results of this study suggest patients would benefit from a multi-disciplinary team needs assessment after medical stabilization to minimize fall risk and disability, and to prevent secondary complications resulting from post-hospital deconditioning due to COVID-19.